Ideación suicida y su relación con la inteligencia emocional en universitarios colombianos (2016)
Introduction: Suicide is a world health problem that is increasing around the world, especially amongst young of committing people. Thoughts about death and ideas of commiting suicide can occur frequently in college students during an academic semester by new life experiences to young people, who are confronted with important social, personal, economic and academic pressures. Some college students succeed by managing these demands effectively while others do not. The emotional competences that allow an individual to successfully cope with adverse situations are known as “emotional intelligence”. The present research work seeks to gain some understanding about the way in which suicidal ideation is related to flaws in the emotional intelligence abilities for coping with adversity. Objectives: To identify the relationship between suicide ideation and emotional intelligence in Colombian college students Methodology: Correlational descriptive study, cross-sectional design. The presence of suicidal ideation was assessed for a sample of 186 college students between 18 and 37 years of age. The Beck Suicidal Ideation Inventory and the Trait Meta Mood Scale -24 were used as measurement instruments. Data analysis is presented in relation to previous findings of suicide studies in Colombia. Results: College students with difficulties for understanding their emotional states, for repairing their negative emotions and for coping with stressors are more likely to develop suicidal thoughts during the academic semester. Conclusion: Emotional intelligence skills are psychological factors that play a fundamental role in the development and maintenance of suicidal thoughts in young Colombian college students.